2003
DOI: 10.1021/tx034101x
|View full text |Cite
|
Sign up to set email alerts
|

Interplay between MRP Inhibition and Metabolism of MRP Inhibitors:  The Case of Curcumin

Abstract: The multidrug resistance proteins MRP1 and MRP2 are efflux transporters with broad substrate specificity, including glutathione, glucuronide, and sulfate conjugates. In the present study, the interaction of the dietary polyphenol curcumin with MRP1 and MRP2 and the interplay between curcumin-dependent MRP inhibition and its glutathione-dependent metabolism were investigated using two transport model systems. In isolated membrane vesicles of MRP1- and MRP2-expressing Sf9 cells, curcumin clearly inhibited both M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
64
0
3

Year Published

2007
2007
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 107 publications
(69 citation statements)
references
References 42 publications
2
64
0
3
Order By: Relevance
“…The last notable type of processes that contributes to the low systemic bioavailability of curcumin and/or the generation of curcumin metabolites entails the association of curcumin with intestinal nondetoxification proteins. In some instances the binding of curcumin to a protein relays an inhibitory effect, as has been shown for several ATP-binding cassette (ABC) transporters (Wortelboer et al, 2003(Wortelboer et al, , 2005Shukla et al, 2009) and CYP isozymes (Volak et al, 2008), whereas in other instances the binding can be both antagonistic and biotransformative, as is the case for, e.g., SULTs (Eaton et al, 1996;Ireson et al, 2002;Volak et al, 2008;Fong et al, 2012), UGTs (Volak et al, 2008;Berginc et al, 2012;Dempe et al, 2012;Fong et al, 2012), and GSTs (Awasthi et al, 2000). With respect to nondetoxifying enzymes, the combined antagonistic and catalytic effects have been demonstrated for curcumin-COX-2 (Hong et al, 2004;Selvam et al, 2005;Griesser et al, 2011) and curcumin-lipoxygenase complexes (Skrzypczak-Jankun et al, 2000;Toth et al, 2000;Hong et al, 2004;Prasad et al, 2004), which result in the formation of 6-hydroxy-1-(4-hydroxy-3-methoxyphenoxy)-3-(4-hydroxy-3-methoxyphenyl)-1,3,3a,6a-tetrahydro-4H-cyclopenta[c]furan-4-one (Fig.…”
Section: Tablementioning
confidence: 98%
See 1 more Smart Citation
“…The last notable type of processes that contributes to the low systemic bioavailability of curcumin and/or the generation of curcumin metabolites entails the association of curcumin with intestinal nondetoxification proteins. In some instances the binding of curcumin to a protein relays an inhibitory effect, as has been shown for several ATP-binding cassette (ABC) transporters (Wortelboer et al, 2003(Wortelboer et al, , 2005Shukla et al, 2009) and CYP isozymes (Volak et al, 2008), whereas in other instances the binding can be both antagonistic and biotransformative, as is the case for, e.g., SULTs (Eaton et al, 1996;Ireson et al, 2002;Volak et al, 2008;Fong et al, 2012), UGTs (Volak et al, 2008;Berginc et al, 2012;Dempe et al, 2012;Fong et al, 2012), and GSTs (Awasthi et al, 2000). With respect to nondetoxifying enzymes, the combined antagonistic and catalytic effects have been demonstrated for curcumin-COX-2 (Hong et al, 2004;Selvam et al, 2005;Griesser et al, 2011) and curcumin-lipoxygenase complexes (Skrzypczak-Jankun et al, 2000;Toth et al, 2000;Hong et al, 2004;Prasad et al, 2004), which result in the formation of 6-hydroxy-1-(4-hydroxy-3-methoxyphenoxy)-3-(4-hydroxy-3-methoxyphenyl)-1,3,3a,6a-tetrahydro-4H-cyclopenta[c]furan-4-one (Fig.…”
Section: Tablementioning
confidence: 98%
“…Several studies have demonstrated that curcumin is capable of inhibiting various ABC transporters (Wortelboer et al, 2003(Wortelboer et al, , 2005Shukla et al, 2009), which is likely to affect the transport kinetics of curcumin and its metabolites in, e.g., enterocytes and hepatocytes, because these cells are replete with multiple ABC transporters (section III.C.2.f). Cancer cells also overexpress multiple ABC transporters (Brozik et al, 2011) that confer multidrug resistance (Tiwari et al, 2011).…”
Section: Tablementioning
confidence: 99%
“…It binds to and inhibits the activity of enzymes, growth factor receptors, metals, albumin, and other molecules. It binds proteins such as P-glycoprotein [68,69], multidrug resistance proteins 1 and 2 (MRP1 and MRP2) [59], glutathione [59], protein kinase C, ATPase [52,53], ErbB2 [61], and alpha1-acid glycoprotein (AGP) [50]. By directly binding small b-amyloid species, curcumin blocks aggregation and fibril formation in vitro and in vivo [51].…”
Section: Curcumin Interacts With Numerous Targetsmentioning
confidence: 99%
“…Although there are no data examining whether curcumin is a substrate of Mrp2, curcumin is known to interact with Mrp2 as an inhibitor. 18,19) Thus, we hypothesized that Mrp2 could be involved in the hepatobiliary excretion of curcumin.…”
mentioning
confidence: 99%